Under Soprano Sky - Sanchez, Sonia (Africa World Press)
Sonia Sanchez (Birmingham, 1934) es autora de una obra muy amplia. Algunos de sus libros son: Homegrils and Handgrenades; Wounded in the House of a Friend; Does Your House Have Lions?; Like the Singing Coming off the Drums; Shake Loose my Skin. Obtuvo el National Endowment for the Arts Fellowship, el PEN Fellowship y el Governor's Award for Excelence in Humanities.